Beyond content delivery: Integrating Microsoft teams and Reflect for affective feedback and enhanced learning readiness - Aris Defiana; Bagus Setiawan; Dedy Agustriyono; Ratih Puspitasari; Dian Ariani (Jurnal Penelitian Ilmu Pendidikan, 2025)
This study explores the integration of Microsoft Teams and its Reflect feature as an innovative learning medium in informatics education, focusing on how real-time emotion visualization can enhance understanding of students' learning readiness. While digital platforms are widely used for content delivery and collaboration, there remains a significant gap in leveraging real-time affective data to adaptively respond to students' emotional states during online learning. Using a qualitative descriptive approach, this research employed participant observation, in-depth interviews, and documentation with 30 Year 11 students and an informatics teacher at SMA Negeri 1 Boyolangu. Findings indicate that emotion visualization via Reflect enables teachers to dynamically adjust instructional strategies based on students' expressed emotional states, thereby increasing engagement, motivation, and perceived learning readiness. This study contributes to the emerging field of affective-aware digital learning environments and underscores the pedagogical value of integrating emotional feedback into technology-enhanced instruction. For future implementation, we recommend broader adoption, teacher training in affective pedagogy, and the exploration of automated emotion-detection technologies to further personalize and responsive learning experiences.